Large‐Scale Fabrication of Highly Emissive Nanodiamonds by Chemical Vapor Deposition with Controlled Doping by SiV and GeV Centers from a Solid Source. Issue 2 (12th December 2019) - De Feudis, Mary; Tallaire, Alexandre; Nicolas, Louis; Brinza, Ovidiu; Goldner, Philippe; Hétet, Gabriel; Bénédic, Fabien; Achard, Jocelyn
Abstract: A new strategy to produce loose chemical vapor deposited nanodiamonds (ND) without the need of a seeded substrate, and that are intentionally doped by silicon vacancy and GeV centers from a solid source is presented. The addition of a low amount of gases such as N2 or O2 during growth is used as a control knob to finely tune the emission intensity of embedded color centers. NDs with a high brightness and a controllable amount of group IV color centers are eventually obtained. Their optical properties at low temperature indicate that this approach can usefully produce dispersed NDs that can deliver suitable optical performance for quantum technologies. Abstract : Chemical vapor deposition plasma technique allows fabricating large‐scale nanodiamonds. Particles can be easily collected and dispersed in a liquid solution, without needing any treatment. The high technique flexibility makes it possible to dope nanodiamonds by the different IV group elements, such as silicon, in order to obtain incorporated color centers. As a result, silicon vacancy center high emissive can be registered.